2022
DOI: 10.1111/and.14562
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of hesperidin on some reproductive parameters in testicular toxicity induced by B isphenol A

Abstract: Bisphenol A (BPA) is one of the chemicals that cause dysfunction and infertility in testicles. Therefore, it is crucial to develop effective treatments against this damage. In this study, the effects of Hesperidin (HESP), a flavonoid in testicular toxicity induced by BPA in rats, on oxidative stress, inflammation, apoptosis, histological damage, spermatogenesis, steroidogenic enzymes and reproductive hormones were investigated. Our study used 52 Sprague Dawley male rats weighing 250–300 g, and four experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
6
7
0
Order By: Relevance
“…Nonetheless, a substantial increase in the serum levels of FSH, LH, and testosterone was observed in PbAc-intoxicated rats pre-treated with HSD. Knowing that OS can lower FSH, LH, and testosterone levels [ 129 ], the restoration of FSH, LH, and/or testosterone levels mediated via HSD might be attributed to its antioxidant effect as previously reported [ 88 , 122 ].…”
Section: Discussionmentioning
confidence: 78%
“…Nonetheless, a substantial increase in the serum levels of FSH, LH, and testosterone was observed in PbAc-intoxicated rats pre-treated with HSD. Knowing that OS can lower FSH, LH, and testosterone levels [ 129 ], the restoration of FSH, LH, and/or testosterone levels mediated via HSD might be attributed to its antioxidant effect as previously reported [ 88 , 122 ].…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, treatment of CBZ-induced rats with HSP markedly decreased renal and testicular IL-6 and TNF-α levels, indicating mitigated inflammation. Previous studies showed the anti-inflammatory effect of HSP in renal tissues [ 16 , 76 ] and testicular tissues [ 77 ]. Under HPO conditions, HSP has been indicated to decrease inflammation in liver and lung as previously reported [ 51 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Co-administration of ELT or HSP showed improvement in testicular structure as previously reported [ 61 , 87 ]. Their protective effect on HPO-induced testicular degeneration may be attributed to the antioxidant abilities, which eliminate free radicals to minimize lipid peroxidation and therefore preserve normal histological structure of testes [ 77 , 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sperm motility was determined by visual estimation for each rat. At least two different areas were evaluated, and the mean motility score was recorded as the final motility score 30 …”
Section: Methodsmentioning
confidence: 99%
“…At least two different areas were evaluated, and the mean motility score was recorded as the final motility score. 30 To determine sperm density, semen samples were diluted 1/100 with physiological saline in a centrifuge tube. Tubes were vortexed at 2500 rpm for 15 s. Approximately 20 μL of semen was transferred to the Thoma counting chamber.…”
Section: Sperm Analysismentioning
confidence: 99%